Markers of operational immune tolerance after pediatric liver transplantation in patients under immunosuppression. (20th May 2013) - Schulz‐Juergensen, S.; Marischen, L.; Wesch, D.; Oberg, H. H.; Fändrich, F.; Kabelitz, D.; Burdelski, M.
Abstract A prospective identification of the estimated 20–50% of pediatric LTX recipients developing operational tolerance would be of great clinical advantage. So far markers of immune tolerance – T‐cell subpopulations or gene expression profiles – have been investigated only retrospectively in successfully weaned patients. Fifty children aged 8–265 months (median 89) were investigated 1–180 months (median 44) after LTX under ongoing immunosuppression. T‐cell subpopulations were measured during regular post‐transplant visits using FACS (Vδ1‐ vs. Vδ2‐γδ‐T cells and Tregs). A Vδ1/Vδ2‐γδ‐T‐cell ratio ≥1.42 previously reported in operational tolerance was found in 12 of 50 (24%) patients. In analogy, a Treg count ≥44 per μL was found in 35 of 50 (70%) patients and a Treg proportion ≥2.23% of CD3+‐T cells in 39 of 50 (78%) patients. Only 9 of 50 patients (18%) fulfilled both criteria. The parameters Vδ1/Vδ2‐γδ‐T‐cell ratio and Tregs were not significantly correlated to each other or with donor type or immunosuppression. Vδ1/Vδ2‐γδ‐T‐cell ratio was more stable in serial examinations compared with Treg analyses. The observed proportion of 18% pediatric LTX patients with potential operational tolerance is in accordance with previous reports. However, clinical experience shows that rejections may happen even after long‐time weaning of immunosuppression. This suggests that operational tolerance is a dynamic process, with uncertain prediction by Vδ1/Vδ2‐γδ‐T‐cell ratio and/or Tregs under immunosuppression.